The use of separate‐level neuraxial anaesthesia for caesarean delivery in a patient with a history of spinal tuberculosis. Issue 2 (12th July 2020) - Kearsley, R.; Elliott, S.; Smith, C.; Stocks, G.
Abstract: We present the case of a 33‐year‐old parturient who required caesarean delivery at 31 weeks' gestation. She had a history of degenerative disease of the lumbar spine secondary to tuberculosis, acquired as a child in India. Her complex medical history also included ischaemic heart disease and obstructive sleep apnoea, and due to this general anaesthesia was considered to be of high risk. However, regional anaesthesia also posed significant challenges because magnetic resonance imaging of the spine showed a partial collapse with subsequent fusion of second and third lumbar vertebral bodies with thoracolumbar kyphosis. Neuraxial anaesthesia was performed with ultrasound guidance for determining levels and depth of epidural space. An epidural was inserted at the T12–L1 interspace and a spinal anaesthetic block was placed at L4–L5. Delivery and recovery were uneventful. This case highlights the safe and effective use of neuraxial anaesthesia in an asymptomatic patient with treated spinal tuberculosis as well as the usefulness of high‐quality imaging of the spine in the decision to perform neuraxial anaesthesia.